Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kinerja Dosen Di Fakultas Ekonomi dan Bisnis Universitas Islam Sumatera Utara - Wahyuni, Neni Sri; Pohan, Rizki Ameilia; Supriadi, Supriadi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
The formulation of the problem in this research is how the work environment influences lecturer performance, how work discipline influences lecturer performance, how the work environment and work discipline influence lecturer performance. The sample in this study is the same as the population, namely 50 lecturers at the Faculty of Economics and Business, Islamic University of North Sumatra, with a total sampling technique or census method. Based on the test results and analysis, it shows that the work environment has a positive and significant effect on lecturer performance, work discipline has a positive and significant effect on lecturer performance, the work environment and work discipline have a positive and significant effect on lecturer performance.